Analysis of Quality in Different Weight Grading Kiwifruits Based on Multivariate Statistical Method - Ke LI; Maowen LIAO; Zixi LIN; Huaiyu YUAN; Cuiping PAN; Yumei LIANG; Yongqing ZHU; Yinglong WU; Huajia LI (Shipin gongye ke-ji, 2023)
Present study investigated the difference between the fruit weight and the quality of 'Hongyang' kiwifruit. The 'Hongyang' kiwiruit from 2 orchards collected from Pujiang and Jintang County of Sichuan Provence were classified according to the weight into five grading (<70 g, 70~90 g, 90~110 g, 110~130 g, >130 g). The soluble solid content, titratable acid content, solid acid ratio, hue angle value, sweet and sour taste, VC content of different grades of fruits were analyzed and compared, and partial least squares-discrimination analysis (PLS-DA) was employed to screen the main differential substances in fruits of different weight grading. The results showed that at the same maturity, the fruit size of 'Hongyang' kiwifruit had an impact on the sweet substances such as sugar (SUC) and SSC, sour substances quinic acid (QA) and VC, but had no significant impact on the color, TA, RTT, etc. The content of SUC and SSC increased with the increase of fruit weight, and the characteristic of fruit with a fruit weight greater than 110 g was sweet. While the content of VC and QA decreased with the increase of fruit weight, and when the fruit weight more than 90 g, the content of VC decreased significantly. Although the content of QA decreased with the increase of fruit weight, it had no significant effect on fruit flavor. According to the above results, sweet and sour substances were the main factors affecting the quality of fruits of different weight grading, and the sweet and sour flavor of fruits with larger weight (> 90 g) was better, but the VC content was lower. The research results provide a scientific basis for the revision of fruit grading standards, production management and rational consumption.